Multi-Response Optimization of Mangosteen Peel Extraction Using Natural Deep Eutectic Solvent and Microwave Assisted Extraction for Anti-Aging - Fitroh Bawa Berkah; Vita Paramita (Vocational College of Universitas Diponegoro, 2025)
The peel of mangosteen (Garcinia mangostana L.) is rich in bioactive compounds, including xanthones, phenolics, flavonoids, anthocyanins, and vitamin C, which have been associated with antioxidant, anti-inflammatory, and anti-aging properties. This study aimed to optimize the extraction of these compounds, particularly xanthones, using Microwave-Assisted Extraction (MAE) in combination with a Natural Deep Eutectic Solvent (NADES) consisting of lactic acid, sodium acetate, and distilled water in a 3:1:2 volume ratio. The extraction process was carried out under varying microwave power levels (300, 375, and 450 Watt) and extraction times (2, 4, and 6 min). Optimization was conducted using Response Surface Methodology (RSM), and the resulting bioactive compound contents were analyzed by UV-Vis spectrophotometry. The optimal extraction conditions were determined at 300 Watt and 4.46 min, resulting in xanthone (1.40%), phenolics (42.43%), flavonoids (1.22%), anthocyanins (1.20%), and vitamin C (2.94%). These findings indicate that NADES-MAE is an effective green extraction technique for maximizing bioactive compounds from mangosteen peel, supporting its potential use in anti-aging product formulations.